A pilot test on a membraneless vacuum preloading method - Sun, Liqiang (2017)
A membraneless vacuum preloading method is proposed in this paper for soft soil improvement. The method offers several advantages over the conventional vacuum preloading in which membrane is used to create the airtight condition and sand blanket layer to distribute vacuum. To assess the effectiveness of the proposed method, a pilot test was conducted at a land reclamation site in Tianjin, China. The ground settlement and the pore water pressure (PWP) at different elevations in soil were measured. After vacuum preloading, the average water content of the soft soils reduced by approximately 12% and the undrained shear strength increased twofold. The average degree of consolidation at the end of the vacuum preloading achieved 85.1% based on the settlement data and 84.5% based on the PWP data. The pilot test data have shown that the proposed method exhibits similar efficiencies to the conventional vacuum preloading method.